Blue overshadows orange: The new president of Ukraine will put domestic policy first - Volodymyr Mychajlovyč Kulyk; Susan Stewart (Stiftung Wissenschaft und Politik (SWP), 2010)
The opposition leader Viktor Yanukovych obtained a clear if narrow victory (49 percent versus 45.5 percent for then Prime Minister Yulia Tymoshenko) and has been sworn in as Ukraine's president for the next five years. He first faces the challenge of acquiring a majority in parliament and forming a government, after which his policies are likely to be dominated by dealing with Ukraine's dire economic situation and by satisfying the interests of his heterogeneous financial supporters. This complex domestic context will shape the priorities of his foreign policy and his approaches to relations with Russia and the European Union
Keywords: 320